2001
DOI: 10.1103/physrevb.63.205305
|View full text |Cite
|
Sign up to set email alerts
|

Nb-induced two-dimensional electron gas onnInAs(110):Anomalous coverage dependence

Abstract: Angle-resolved photoelectron spectroscopy was used to determine the coverage dependence of the Nbinduced Fermi-level shift and the formation of a two-dimensional electron gas ͑2DEG͒ on n-type InAs͑110͒. The maximum Fermi-level shift of 300 meV was achieved at a Nb coverage of 20%, which is a factor of 70 higher than expected from the surface doping model. Scanning tunneling microscopy images reveal the formation of Nb clusters ͑1-4 atoms͒ at room temperature, however, the resulting reduced Nb-Nb distance canno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…We argue that the original polarisation of the surface is broken by adsorption of an ordered metallic layer on top of the surface, which changes the charge density and bandbending profile along the z-coordinate. In addition to the depolarising effect we suggest that the Pb donor level experience a shift due to hybridisation within the overlayer in agreement with previous suggestions [20].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…We argue that the original polarisation of the surface is broken by adsorption of an ordered metallic layer on top of the surface, which changes the charge density and bandbending profile along the z-coordinate. In addition to the depolarising effect we suggest that the Pb donor level experience a shift due to hybridisation within the overlayer in agreement with previous suggestions [20].…”
Section: Introductionsupporting
confidence: 89%
“…The anomalous coverage dependence was discussed by Getzlaff et al for the case of Nb on InAs(1 1 0) [20]. It was proposed that hybridisation of the donor levels within adatom clusters, which depends on the cluster size, plays an important role on the ionisation probability of the adatoms.…”
Section: Resultsmentioning
confidence: 96%
“…The charge transfer to the accumulation layer and the charge arrangement must be connected to the sharpness of the interface, which is at its highest when the surface reconstruction is fully developed. Furthermore, it has been put forward by Getzlaff et al [22], that the donor level from the metal varies with coverage due to hybridization. This hybridization would then be most favorable within ordered monolayers and less favorable when the metal coverage increases or the surface order is poor.…”
Section: Resultsmentioning
confidence: 98%
“…It is well known that a two-dimensional electron gas (2DEG) can be easily formed on the surface of InAs and InSb. Photoelectron spectroscopy measurements have shown that the position of the Fermi level lies above the conduction-band minimum at cleaved (110) surfaces with various kinds of adsorbed materials [24,25]. Recently the present authors have performed magnetotransport measurements on inversion layers formed on cleaved surfaces of p-type InAs [26,27] and InSb [28] covered with submonolayers of Ag or alkali metals.…”
mentioning
confidence: 99%